2009
DOI: 10.1094/phyto-99-8-0974
|View full text |Cite
|
Sign up to set email alerts
|

Geostatistical Analysis of the Spatiotemporal Dynamics of Powdery Mildew and Leaf Rust in Wheat

Abstract: Plant diseases are dynamic systems that progress or regress in spatial and temporal dimensions. Site-specific or temporally optimized disease control requires profound knowledge about the development of each stressor. The spatiotemporal dynamics of leaf rust (Puccinia recondite f. sp. tritici) and powdery mildew (Blumeria graminis f. sp. tritici) in wheat was analyzed in order to evaluate typical species-dependent characteristics of disease spread. During two growing seasons, severity data and other relevant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 32 publications
1
6
0
1
Order By: Relevance
“…As expected leaf rust severities were higher in the lowlands whereas stripe rust was more severe in the highlands. Relationships between monthly precipitation and disease development are both region-and pathogen-specific as previously shown by Franke et al (2009).…”
Section: Discussionsupporting
confidence: 65%
“…As expected leaf rust severities were higher in the lowlands whereas stripe rust was more severe in the highlands. Relationships between monthly precipitation and disease development are both region-and pathogen-specific as previously shown by Franke et al (2009).…”
Section: Discussionsupporting
confidence: 65%
“…Several factors contribute to the increase and spread of powdery mildew, including the available inoculum, weather conditions, geographic characteristics, host resistance, host growth stage, and weather conditions (Franke et al, 2009;Mount and Slesinski, 1971;Nelson and Campbell, 1993;Roelfs, 1972;Tubajika et al, 2004). The two-year study on the effective dispersal distance of the fungus indicated that the pathogen can spread more than 500 cm from the initial infection site in one infection cycle.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a large number of studies were made on plant disease epidemics using spatial pattern analysis in order to relate the observed characteristics of epidemics to the underlying ecological and pathological processes [100][102]. However, specific studies on the spatial pattern analysis of the pedoclimatic factors affecting plant diseases are lacking in the literature.…”
Section: Discussionmentioning
confidence: 99%